The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.npp.1300611
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lithium Administration to Rats Selectively Modifies 5-HT2A/2C Receptor-Mediated Brain Signaling Via Arachidonic Acid

Abstract: The effects of chronic lithium administration on regional brain incorporation coefficients k* of arachidonic acid (AA), a marker of phospholipase A 2 (PLA 2 ) activation, were determined in unanesthetized rats administered i.p. saline or 1 mg/kg i.p. (7)-1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane hydrochloride (DOI), a 5-HT 2A/2C receptor agonist. After injecting [1-14 C]AA intravenously, k* (brain radioactivity/integrated plasma radioactivity) was measured in each of 94 brain regions by quantitative autora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 117 publications
(152 reference statements)
6
21
0
Order By: Relevance
“…Moreover, a fraction of the AA that is released by PLA 2 activation will be rapidly reincorporated into phospholipid, whereas the remainder will be lost by conversion to eicosanoids or other products, or by b-oxidation (82,83). Unesterified AA in plasma rapidly replaces the amount lost, and this replacement is proportional to PLA 2 activation (84,85). In our experiments, BEL alone inhibited free AA, but increased free AA when COX was inhibited at the same time.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, a fraction of the AA that is released by PLA 2 activation will be rapidly reincorporated into phospholipid, whereas the remainder will be lost by conversion to eicosanoids or other products, or by b-oxidation (82,83). Unesterified AA in plasma rapidly replaces the amount lost, and this replacement is proportional to PLA 2 activation (84,85). In our experiments, BEL alone inhibited free AA, but increased free AA when COX was inhibited at the same time.…”
Section: Discussionmentioning
confidence: 71%
“…These regions included visual cortex layers I, IV, and VI, lateral habenular nucleus, medial geniculate nucleus, and inferior colliculus, which belong to central auditory and visual pathways (Brodal, 1981). We reported this observation (Basselin et al, 2003(Basselin et al, , 2005b, and suggested that it may underlie lithium's ability in human subjects to increase the amplitudes of P1/N1 components of auditory-evoked responses and of 65-P95 and P95-N125 components of visual-evoked responses (Fenwick and Robertson, 1983;Hegerl et al, 1990;Ulrich et al, 1990). In 65/83 regions, NMDA increased k* significantly in the control diet but not in the LiCl-fed rats.…”
Section: Physiological Parametersmentioning
confidence: 81%
“…As k* responses to arecoline and quinpirole represent PLA 2 activation coupled to M 1, 3,5 and D 2 -like receptors, respectively (Bayon et al, 1997;DeGeorge et al, 1991;Hayakawa et al, 2001;Nilsson et al, 1998;Rapoport, 2001;Vial and Piomelli, 1995), the arecoline and quinpirole data suggest that lithium affects M 1,3,5 and D 2 -like receptor-mediated activation of PLA 2 in opposite ways. In contrast, LiCl has a more complex effect on k* responses in rats to DOI, an agonist of 5-HT 2A/2C receptors that also can be coupled to PLA 2 (Basselin et al, 2005;Felder et al, 1990;Qu et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…This may explain why lithium does not reduce k* responses to the muscarinic receptor agonist arecoline (it even increases them), nor to the 5-HT 2A/2C receptor agonist, DOI, in most brain regions (responses are blocked by lithium in visual and auditory areas in which baseline values of k* are elevated) (Basselin et al, 2005(Basselin et al, , 2003b.…”
Section: Discussionmentioning
confidence: 99%